PENGARUH PEMBERIAN FLUSHING PAKAN TERHADAP CAPAIAN HASIL INSEMINASI BUATAN PADA DOMBA DI DESA TANJUNGHARJO, NANGGULAN, KULONPROGO - Utomo, Setyo (Universitas Sebelas Maret, 2009)
The aim of this research was to solve the management reproduction problem of doe in Tanjungharjo village. This reseaarch was an aplication of estrous syncronization technology using proviously flushing. Egg yolk which used for the flushing was given for five times at pre matting phase. This research showed that there was no significant effect between flushing and not flushing. All the doe were estrous with syncronization estrous and all of them were pregnant. It could be concluded that flushing was not recommended if there were sufficiant nutrition in quality and quantity